A practical synthesis of the flavone, scutellarein. (1st March 2017) - Wang, Qian; Liao, Xia-Li; Xiang, Cheng; Yang, Jian
A practical and economical five-step synthesis of the flavone scutellarein has been achieved in 60% overall yield using the available and cheap 2, 6-dimethoxy-1, 4-benzoquinone as starting material. The reaction sequence involved reduction to the corresponding quinol, Friedel-Crafts acetylation, Claisen-Schmidt condensation with p-methoxybenzaldehyde, cyclisation and demethylation. The procedure is operationally simple and amenable to scale-up synthesis.